2022
DOI: 10.3390/chemistry4010004
|View full text |Cite
|
Sign up to set email alerts
|

Valence-, Dipole- and Quadropole-Bound Electronically Excited States of Closed-Shell Anions Formed by Deprotonation of Cyano- and Ethynyl-Disubstituted Polycyclic Aromatic Hydrocarbons

Abstract: Dicyano-functionalized benzene and naphthalene anion derivatives exhibit a relatively rich population of electronically excited states in stark contrast to many assumptions regarding the photophysics of anions in general. The present work has quantum chemically analyzed the potential electronically excited states of closed-shell anions created by replacing hydrogen atoms with valence-bound lone pairs in benzene and naphthalene difunctionalized with combinations of -CN and -C2H. Dicyanobenzene anion derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…25,26 Very recently, the reaction of deprotonation of all three CEBs was characterized with electronic structure calculations. 27 Finally, the relative energies of the CEB isomers were calculated in Buchanan et al 15 and their rotational constants were predicted using the ''Lego brick'' approach in Melli et al 14 We summarize here our investigations on the three CEB species: their millimeter-wave spectra have been recorded using a chirped-pulse Fourier-transform and a source-frequency modulation spectrometers, and the spectral assignments were supported by quantum chemical calculations performed using the ''Lego brick'' approach. For each species, pure rotational transitions have been assigned in the ground vibrational state as well as in excited vibrational ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Very recently, the reaction of deprotonation of all three CEBs was characterized with electronic structure calculations. 27 Finally, the relative energies of the CEB isomers were calculated in Buchanan et al 15 and their rotational constants were predicted using the ''Lego brick'' approach in Melli et al 14 We summarize here our investigations on the three CEB species: their millimeter-wave spectra have been recorded using a chirped-pulse Fourier-transform and a source-frequency modulation spectrometers, and the spectral assignments were supported by quantum chemical calculations performed using the ''Lego brick'' approach. For each species, pure rotational transitions have been assigned in the ground vibrational state as well as in excited vibrational ones.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Very recently, the reaction of deprotonation of all three CEBs was characterized with electronic structure calculations. 27 Finally, the relative energies of the CEB isomers were calculated in Buchanan et al 15 and their rotational constants were predicted using the “Lego brick” approach in Melli et al 14…”
Section: Introductionmentioning
confidence: 99%
“…Although para -DCNB does not possess a permanent dipole moment due to its symmetry, the two cyano moieties make ortho- and meta -DCNB have relatively large dipole moments, making them visible by radio astronomy . Kinetic studies involving CN + toluene (C 6 H 5 CH 3 ) by Messinger et al have shown that the addition of a CN group to a substituted benzene, such as C 6 H 5 CH 3 , has a similar reaction rate efficiency as that produced with the addition of CN directly to the benzene ring itself to form benzonitrile. , Based on the Messinger et al kinetic study, Chitarra et al, despite failing to detect DCNBs in the GBT Observations of TMC-1: Hunting Aromatic Molecules (GOTHAM), estimated that the column densities of ortho- and meta- DCNB could be as high as 2 × 10 10 cm –2 , which is below the benzonitrile column density of 17.3 –1.00 +0.85 × 10 12 cm –2 , to yield a DCNB/C 6 H 5 CN abundance ratio of ∼1:100 .…”
Section: Introductionmentioning
confidence: 99%
“…30 The vibrational information provided by the negative ion spectra of radical anions of these cyano-functionized PAHs is important since regions of high electron densities and low UV photon flux are considered to exist predominantly as negatively charged ions. 31 The change from negative or very low electron affinities (EAs) corresponding to unbound anions on moving from benzene and naphthalene to higher EAs, above 0.5 eV, as the molecular size of the PAH increases has been found to attract the formation of long-lived, valence and dipole-bound PAH anions, 32 providing a fertile ground for investigating the role played by such stable PAH anions in chemical reaction networks in dense interstellar clouds.…”
Section: Introductionmentioning
confidence: 99%